The Development of Russian-Chinese Expert Contacts on International Relations - I. A. Safranchuk (Vestnik MGIMO-Universiteta)
Abstract: This article is devoted to the contacts of Russian and Chinese experts on international relations and to the visit of MGIMO-University delegation to Beijing in June 2015. The article studies the major tracks of expert dialogue between Russian and Chinese experts on contemporary international affairs: the situation in the Near and Middle East, the developments in Eurasia, the major regional conflicts. The particular attention in the Russian-Chinese expert debates is devoted to the topic of Eurasia and the perspective for agreed implementation of Russia-sponsored Eurasian Economic Union and China-sponsored Economic belt of Silk Road. The article dwells upon the key issues in the Russian-Chinese dialogue on the Eurasian affairs. Additionally the article unveils the proposals by the US experts, concerning the development of Russian-Chinese dialogue on these matters. In 2015 the US experts developed new ideas on the regional issues in Eurasia, they offer to coordinate the Chinese project Economic belt of Silk Road and the US project of New Silk Road. In 2015 the historical topic gained momentum in the Russian-Chinese expert debates. Now Russia and China jointly oppose the attempts of some countries to revisit the results of World War II. However while Russia and China are both committed to the traditional interpretations of World war II and resist any revisionism of those results, still the Chinese experts argue in favor of greater appreciation of the role and contribution by China to the victory over fascism and militarism in World war II. The article also overviews interesting discussions between Russian and Chinese experts on the reform of global governance and the formation of the new world order.